Answer:
800
Step-by-step explanation:
ROund 39 to 40 and 18 to 20.
This results in 40 x 20=800.
Answer:
A
Step-by-step explanation:
Answer:
(3x+1)(x+3) is the factorised form for the expression.
Step-by-step explanation:
:3
x
2
+
10
x
+
3
We can Split the Middle Term of this expression to factorise it.
In this technique, if we have to factorise an expression like
a
x
2
+
b
x
+
c
, we need to think of 2 numbers such that:
N
1
⋅
N
2
=
a
⋅
c
=
3
⋅
3
=
9
and,
N
1
+
N
2
=
b
=
10
After trying out a few numbers we get:
N
1
=
9
and
N
2
=
1
9
⋅
1
=
9
, and
9
+
(
1
)
=
10
3
x
2
+
10
x
+
3
=
3
x
2
+
9
x
+
1
x
+
3
=
3
x
(
x
+
3
)
+
1
(
x
+
3
)
(
3
x
+
1
)
(
x
+
3
)
is the factorised form for the expression.
is the factorised form for the expression.
Hi! Your answer is below!
Answer- Here's a simple model:
<span><span>X⟶f⟶Y
This is just something to help you out! I found it while searching on the internet! I have no Idea what the answer is, but in my defense, I think it's going to be choice 3!
Srry if I couldn't help! Glad if I could help!</span></span>
Answer:
6.5e^(i·(-157.38°)) ≈ 6.5e^(-2.7468i)
Step-by-step explanation:
A suitable calculator can find the value of this ratio for you.
((2+3i)/(1-i))² = -6 -2.5i ≈ 6.5∠-157.38° ≈ 6.5e^(-2.7468i)
__
The second attachments shows the calculator set to radian mode for the angle measure.